1997
DOI: 10.1021/jo961598p
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium Complex-Catalyzed Reaction of Isocyanoacetate andN-Sulfonylimines:  Stereoselective Synthesis ofN-Sulfonyl-2-Imidazolines

Abstract: Ruthenium(II)-catalyzed reaction of N-sulfonylimines with methyl isocyanoacetate proceeds efficiently under neutral, mild conditions to give trans-2-imidazolines stereoselectively in high yields. 2,3-Diamino acids can be easily acquired via the hydrolysis of the imidazolines in excellent yields. A possible mechanism for the ruthenium-catalyzed aldol reaction of the imines under neutral conditions is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(28 citation statements)
references
References 47 publications
0
27
0
1
Order By: Relevance
“…In all cases, the trans-2-imidazolines were obtained with high selectivity and yield [6]. The results indicate that Ru(II)-complex-catalysed aldol reactions of N-sulfonylimines are highly ef®cient in yield and stereoselcetivity under neutral condition.…”
Section: Aldol Reactions With Iminesmentioning
confidence: 80%
See 1 more Smart Citation
“…In all cases, the trans-2-imidazolines were obtained with high selectivity and yield [6]. The results indicate that Ru(II)-complex-catalysed aldol reactions of N-sulfonylimines are highly ef®cient in yield and stereoselcetivity under neutral condition.…”
Section: Aldol Reactions With Iminesmentioning
confidence: 80%
“…The imidazolines obtained by this reaction can be used in the the synthesis of various substituted 2,3-diamino acids or diamino alcohols (6), which are constituents of some peptidic antibiotics as well as other biologically active molecules. Optically pure 2,3-diamino acids can also be obtained by the simple hydrolysis and deprotection of these chiral 2-imidazolines that were upgraded by crystallisation (Scheme 4).…”
Section: Aldol Reactions With Iminesmentioning
confidence: 99%
“…Notwithstanding, this reaction is particularly interesting, since condensation of imines with isocyanides leads to 2-imidazolines, which can easily be converted to a,b-diamino acids, which represent [43] a class of biologically important compounds. Although, this important condensation reaction could be performed using various sulfonimines (2) and isocyanoacetate (3) in the presence of gold, [44][45][46] ruthenium [47] and copper [48] catalysts, reports on palladium-catalyzed reactions are very scarce. [44,47] This can be explained by the fact that the palladium-catalyzed coupling of imines with isocyanides was characterized as a slow and unselective process.…”
Section: Introductionmentioning
confidence: 99%
“…Although, this important condensation reaction could be performed using various sulfonimines (2) and isocyanoacetate (3) in the presence of gold, [44][45][46] ruthenium [47] and copper [48] catalysts, reports on palladium-catalyzed reactions are very scarce. [44,47] This can be explained by the fact that the palladium-catalyzed coupling of imines with isocyanides was characterized as a slow and unselective process. [44,47] We have now found that palladium pincer complexes show a relatively high catalytic activity in the coupling of sulfonimines with isocyanoacetate; and that the stereoselectivity of the process is highly dependent on the electronic properties of the applied pincer complex catalysts (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation